Characteristics of Peripheral Lymphocyte Subsets in Patients With Acute-On-Chronic Liver Failure Associated With Hepatitis B - Li, Juan; Hu, Chun-Hua; Chen, Yi; Zhou, Mi-Mi; Gao, Zhi-Jie; Fu, Meng-Jun; Wang, Jing; Li, Jian-Zhou; Chen, Tian-Yan; Zhao, Ying-Ren; He, Ying-Li (Frontiers in Medicine, 2021)
Background & Aims Acute-on-chronic liver failure (ACLF) is a rare, but dramatic clinical syndrome. There is substantial evidence suggesting that immunity-mediated inflammation plays an important role in HBV-ACLF. Our aim was to characterize the proportion and cell counts of peripheral blood lymphocyte subsets in acute-on-chronic liver failure patients caused by HBV infection. Methods 117 patients were enrolled in this study, including those with HBV‐related ACLF (HBV‐ACLF; n=70), and HBV related non-ACLF patients (HBV non-ACLF; n=47). Demographics, clinical and laboratory data at hospital admission were retrospectively analyzed. The percentage and cell count of peripheral lymphocyte subsets were evaluated by flow cytometry. Comparison analysis was performed by t test or nonparametric Mann–Whitney U test. Actuarial probabilities of death were calculated by the Kaplan‐Meier method. Results Both circulating lymphocyte count and lymphocyte percentage were significantly reduced in patients with HBV-ACLF (P＜0.001). The CD8+ T cell, CD4+ T cell, and CD16+CD56+ NK cell counts were significantly decreased in HBV-ACLF. Consistently, flow cytometric analysis showed that CD8+ T cell counts were significantly decreased in non-survivors, while no significant differences were found in CD4+ T cell, CD19+ B cell or CD56+CD16+ NK cell counts. Furthermore, the group with the lower CD8+ T cell count displayed a significantly higher mortality rate compared with the group with the higher CD8+ T cell count.